2021
DOI: 10.1558/jircd.20902
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative storytelling with a person with aphasia

Abstract: Introduction: This study explores practices employed by a person with aphasia (PWA) and his wife to organize collaborative storytelling in a multiparty interaction. We identify practices that further the PWA’s agency – his impact on action – while he is telling a story together with his wife. Method: Using conversation analysis (CA), we carried out a case study of a successful storytelling sequence involving a 39-year-old man with anomic aphasia during a conversation with friends. Analysis: The PWA contributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The questioning format, the continuers and the scaffolding yield opportunities for the student to control the turn, which mirrors Antaki and Crompton (2015) who found that supportive actions can create an agentive discourse in which individuals with disabilities are able to display communicative competence and agency. As Killmer et al (2021) suggested, the opportunity to display agency succeeds presenting communicative competence: our analysis showed that agency in SGD-mediated interaction assumed communicative competence.…”
Section: Concluding Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…The questioning format, the continuers and the scaffolding yield opportunities for the student to control the turn, which mirrors Antaki and Crompton (2015) who found that supportive actions can create an agentive discourse in which individuals with disabilities are able to display communicative competence and agency. As Killmer et al (2021) suggested, the opportunity to display agency succeeds presenting communicative competence: our analysis showed that agency in SGD-mediated interaction assumed communicative competence.…”
Section: Concluding Discussionsupporting
confidence: 51%
“…Adam's scaffolding practice, positioning the activated SGD with a preferred response within reach for Rickard, creates an ‘agentive discourse’ in which communicative competence can be displayed (Antaki and Crompton, 2015; Killmer et al 2021). Rickard displays communicative competence and provides a well-timed second pair part of the question-answer sequence as he presses the SGD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations